Cast away [videorecording (DVD)] - Hanks, Tom; Hunt, Helen, 1963-; Searcy, Nick (20th Century Fox Home Entertainment, 2002)
Chuck Noland, a FedEx systems engineer, finds his ruled-by-the-clock existence ended when a harrowing plane crash leaves him isolated on a remote island. As Chuck struggles to survive, he finds that his own personal journey has only just begun.